2013
DOI: 10.1038/srep03131
|View full text |Cite
|
Sign up to set email alerts
|

CDKAL1 gene rs7756992 A/G polymorphism and type 2 diabetes mellitus: a meta-analysis of 62,567 subjects

Abstract: The Cyclin-dependent kinase 5 regulatory subunit-associated protein 1-like (CDKAL1) gene rs7756992 A/G polymorphism has been suggested to be associated with type 2 diabetes mellitus (T2DM), but the individual studies results are still controversial. To explore the association of CDKAL1 gene rs7756992 A/G polymorphism with T2DM, a meta-analysis involving 62,567 subjects from 21 separate studies was conducted. In the whole population, a significant association was found between CDKAL1 gene rs7756992 A/G polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
2
8
0
6
Order By: Relevance
“…Later, it was replicated repeatedly in Caucasian populations [34]. Recently, a metaanalysis of this SNP in 62 567 individuals also confirmed its strong association with Type 2 diabetes risk in Caucasians and Asians, but not in Africans [35]. We also replicated ZFAND3/rs9470794 SNP in our sample.…”
Section: Discussionsupporting
confidence: 78%
“…Later, it was replicated repeatedly in Caucasian populations [34]. Recently, a metaanalysis of this SNP in 62 567 individuals also confirmed its strong association with Type 2 diabetes risk in Caucasians and Asians, but not in Africans [35]. We also replicated ZFAND3/rs9470794 SNP in our sample.…”
Section: Discussionsupporting
confidence: 78%
“…Sensitivity analysis was performed by removing one study at a time to ensure that our findings were not driven by any single study. The evaluation of potential publication bias was performed using the Begg's funnel plots and Egger's test 18 . All ORs for the five genetic models will be compared with each other, and the genetic model with the greatest OR and statistical significant result will be the inheritance model that is most likely to contribute the risk of lung cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have verified that the number of fusion events during first-phase insulin release is reduced in vitro, leading to impaired insulin exocytosis in CD-KAL1-deficient mice [6,15]. CDKAL1 is highly expressed in the human pancreas, skeletal muscle, and brain tissue and can especially inhibit cyclin-dependent kinase 5 (CDK5) activity [16][17][18]. Inhibition of the CDK5 activity enhances insulin secretion in high glucose conditions but not low glucose conditions in MIN6 cells and pancreatic islets [16].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the CDK5 activity enhances insulin secretion in high glucose conditions but not low glucose conditions in MIN6 cells and pancreatic islets [16]. Ubeda et al found that in a high glucose internal environment, CDK5 overactivity can decrease the insulin release rate, reduce insulin production, and inhibit insulin gene expression [17,19]. The CDKAL1 gene variant rs9356744 probably activates CDKAL1 function and inhibits CDK5 activity in high-glucose internal environments, leading to enhanced insulin secretion, thus reducing the levels of 2hPG and HbA1c.…”
Section: Discussionmentioning
confidence: 99%